Offerors’ Image in The Relationships Context – Final Purchasers’ Point of View - Agnieszka Izabela BARUK (Communications of International Proceedings, 2020)
The article has theoretical and empirical character. Its aim was to identify the importance attributed by purchasers to good mutual relationships with offerors and to identify the importance of the perception of offerors as entities listening to purchasers’ opinions and profiting from purchasers’ spontaneous willingness to cooperate with offerors. The results of the cognitive-critical analysis of the world literature indicate a cognitive and research gaps. In order to reduce them, empirical studies were conducted. The survey method was used to gather primary data. The collected data were subjected to quantitative analysis (including statistical analysis methods). Between the importance attributed to good relationships with offerors and the perception of them, a statistically significant relationship was identified for each of the three analysed groups of offerors. The perception of offerors turned out to be a feature differentiating respondents’ opinions on the importance of good relationships with offerors for producers and traders. The perception of offerors turned out to be a feature differentiating forms of prosumer activity undertaken by the respondents for three behaviours of an inter-purchase nature. The results obtained have a significant cognitive and applicability value because the aspects presented in this article have not been analysed so far.
Keywords: Offeror; Image; Relationships; Final Purchaser.